PENGARUH FASILITAS DAN CITA RASA DALAM MEMPENGARUHI LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN PADA RUMAH MAKAN LESEHAN IKAN BAKAR BU TATIK DI KAPONGAN KABUPATEN SITUBONDO - Zulfa, Nailas; Arief, Mohammad Yahya; Harisandi, Yudhistira (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is generally seen as the activity of creating, introducing, and delivering goods and services to consumers. Marketing is the process by which companies create value for customers and build strong customers to capture value from customers in return. Marketing is an organizational function and a set of processes for creating, communicating and delivering value to customers and managing customer relationships in ways that benefit the organization and its interests in particular. for customers of Bu Tatik's grilled fish lesehan restaurant by improving the culinary arts in Situbondo Regency. The purpose of this study was to analyze and examine the influence of facilities and taste in influencing consumer loyalty through consumer satisfaction at the restaurant Lesehan Ikan Bakar Bu Tatik in Kapongan, Situbondo Regency. The population in this study are consumers at the Restaurant Lesehan Ikan Bakar Bu Tatik in Kapongan, Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Facilities have a positive but not significant effect on consumer satisfaction, Taste has a significant positive effect on consumer satisfaction, Facilities have a significant positive effect on consumer loyalty, Taste has a significant positive effect on consumer loyalty, Consumer satisfaction has a positive significant effect on consumer loyalty, facilities on consumer loyalty through consumer satisfaction have a positive but not significant effect, taste on consumer loyalty through consumer satisfaction has a significant positive effect.